Performance Evaluation of Faecal Sludge Treatment Plant: Efficiency, Compliance, and Operational Challenges - D.C., Milan; Maharjan, Rabin; Lekhak, Basant (Journal of Engineering Issues and Solutions, 2025)
In today’s world, the Faecal Sludge Management (FSM) is an important issue needed to be addressed in a sustainable way. Faecal sludge has both solid and liquid matters and its management (FSM) refers to the emptying, transportation, treatment and safe disposal. Many plants of FSM are being designed and constructed but are not working effectively as designed. To know about the actual field performance to designed components, this study was conducted at Charali Faecal Sludge Treatment Plant. This plant consists of Screening Chamber, Drying Beds (DB), Anaerobic Baffle reactor (ABR), Anaerobic Filter (AF) and Planted Gravel Filter (PGF) in series respectively where, solid is separated in drying bed and rest treats the effluents. Liquid effluent is treated in ABR and AF anaerobically then PGF provides the final treatment aerobically through plant uptake. The raw sludge sampled in inlet of the plant shows low alkalinity with average pH of 8.1. Average individual Biological Oxygen Demand (BOD) removal efficiency of the ABR and PGF were found 20.42%, and 57.83% respectively whereas overall BOD removal efficiency of plant was found 79.71%. But in accordance to design report, average removal efficiencies of the ABR and PGF were 64% and 84.33%. This variation suggests that the plant is working inefficiently contrary to design expectations. BOD of final effluent from treatment plant was found 117 mg/L that exceeds the standard limit for discharge to on water bodies or land. BOD removal efficiency of DB and AF were also analyzed and found 17.68% and 26.55% respectively with 79.71 % overall removal efficiency of treatment plant. For Total Nitrogen, removal efficiencies of DB, ABR, AF and PGF were found 26.78%, 17.73%, 24.09% and 35.16% respectively.